The ostrich mycoplasma Ms02 partial genome assembly, bioinformatic analysis and the development of three DNA vaccines - Strydom, Marliz (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.